1991
DOI: 10.1007/bf01744946
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mammary tumorigenesis in virgin rats by adoptive transfer of splenocytes from parous donors

Abstract: Splenocytes from parous rats have been previously found to have cytotoxic activity against mammary tumor cells in vitro. Experiments were carried out to determine if this pregnancy-induced cytotoxic nature of the splenocytes is inherent and transferable. Splenocytes from parous rats wer adoptively transferred to a group of virgin rats. Another group of age-matched, virgin rats received splenocytes from virgin donors in a similar way. After a period of rest, at the age of 55 days, the rats belonging to both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In animal models, at least, this has already been demonstrated in that splenocytes from parous rats compared to those from nulliparous rats have revealed a significantly higher cytotoxic activity against mammary tumors in vivo [ 18 ]. Furthermore, the adoptive transfer of those splenocytes from parous rats into virgin counterparts resulted in a reduced carcinogen-induced mammary tumorigenesis [ 19 ]. Additional studies showed that this pregnancy-associated cytolysis was mediated by T cells in a cell contact-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, at least, this has already been demonstrated in that splenocytes from parous rats compared to those from nulliparous rats have revealed a significantly higher cytotoxic activity against mammary tumors in vivo [ 18 ]. Furthermore, the adoptive transfer of those splenocytes from parous rats into virgin counterparts resulted in a reduced carcinogen-induced mammary tumorigenesis [ 19 ]. Additional studies showed that this pregnancy-associated cytolysis was mediated by T cells in a cell contact-dependent manner.…”
Section: Discussionmentioning
confidence: 99%